Analytical approaches to evaluate risk factors of multimorbidity: a systematic scoping review protocol - Alex Lewin; Poppy Alice Carson Mallinson; Sanjay Kinra; Judith Lieber; Chaisiri Angkurawaranon; Hirotomo Yamanashi; Chanchanok Aramrat; Nutchar Wiwatkunupakarn; Nick Birk; Wenbo Song; Mika Matsuzaki; Elliott Rogers (BMJ Open)
Introduction Understanding causal risk factors that contribute to the development of multimorbidity is essential for designing and targeting effective preventive strategies. Despite a large body of research in this field, there has been little critical discussion about the appropriateness of the various analytical approaches used. This proposed scoping review aims to summarise and appraise the analytical approaches used in the published literature that evaluated risk factors of multimorbidity and to provide guidance for researchers conducting analyses in this field.Methods and analysis We will systematically search three electronic databases—Embase, Global Health and MEDLINE, as well as the reference lists of identified relevant review articles, from inception to September 2024. We will screen titles and abstracts using the artificial intelligence-aided software ASReview, followed by screening for eligible articles in full text and extracting data. We will then categorise the analytical approaches used across studies, provide a comprehensive overview of the methodology and discuss the potential strengths and limitations of each analytical approach.Ethics and dissemination We will undertake a secondary analysis of published literature; therefore, ethical approval is not required. The results will be disseminated through an open-access, peer-reviewed publication. This systematic scoping review will serve as a guide for researchers in selecting analytical approaches for aetiological multimorbidity research, thereby improving the quality and comparability of research in this field.